Robert L. Heilbroner. Business civilization in decline. Nueva York : W. W. Norton and Co., 1976. 127 p. - Hodara B., Joseph (Estudios Demográficos y Urbanos, 1976)
ROBERT L. HEILBRONER, Business Civiiization in Decline, Nueva York, W. W. Norton and Co. 1976.